Single‐center prospective study of Plummer–Vinson syndrome. Issue 7 (30th July 2015) - Goel, A.; Lakshmi, C. P.; Bakshi, S. S.; Soni, N.; Koshy, S.
Summary: Post‐cricoid web is an uncommon cause for dysphagia and is most frequently reported in middle‐aged women. Triad of web, iron deficiency anemia (IDA), and dysphagia is known as Plummer–Vinson syndrome (PVS). Literature on PVS is very limited. Here we report the first prospective study of PVS with predefined diagnostic criteria and management plan. Adults with dysphagia or those incidentally found to have esophageal web were prospectively enrolled between July 2011 and June 2013. Participants were evaluated with hemogram, barium swallow, and esophagogastroduodenoscopy. PVS was diagnosed if a person had IDA and a post‐cricoid web in barium swallow and/or endoscopy. Patients were managed with dilation using through‐the‐scope controlled radial expansion balloon followed by oral iron and folic acid supplementation. Thirty‐seven patients (age, median [range] 40 [19–65] years; 32 [86%] women) were enrolled. Thirty‐one symptomatic patients had dysphagia grade 1 ( n = 12, 39%), 2 ( n = 13, 42%), and 3 ( n = 6, 19%) for a median (range) duration of 24 (4–324) months. Barium swallow, done in 29, showed web in 25 which were either circumferential or anterior in position. Twenty‐nine (29/31, 94%) patients had complete and two had partial response after the first session of endoscopic dilatation without any complication. Dysphagia recurred in three (10%) of the 30 patients who were followed for a median (range) of 10 (1–24) months. Esophageal‐web related dysphagia in patients with PVS responds favorably after single session of endoscopic dilation.